Optical and generation characteristics of new nonlinear Ba2Ga8GeS16 and Ba2Ga8(GeSe2)S14 crystals for the mid-IR range. (1st March 2022) - Badikov, V V; Badikov, D V; Shevyrdyaeva, G S; Laptev, V B; Melnikov, A A; Chekalin, S V
Abstract: Ba2 Ga8 GeS16 and Ba2 Ga8 (GeSe2 )S14 single crystals oflarge size and good optical quality have been grown for the first time. Their linear optical characteristics–transmission spectra in the range of 0.3–25 mm, dispersion of principal refractive indices, and birefringence — have been measured. Irradiation of the crystals by 100-fs laser pulses with a wavelength of 8.3 mm initiated secondharmonic generation with an efficiency comparable with that obtained for the AgGaS2 crystal.